RETRACTED: Conditions of adaptation in teaching environmental disciplines at the university - Polozova Olga; Blinova Maria; Zimina Irina; Gavrilova Maria (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001